Yesus, Al-Ghazali Dan Diriku: Keteladanan Yesus Di Ihya' Ulum Ad-Din Menurut Perspektif Teologi Komparatif - Sukarno (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2022)
Abstract: Jesus is understood in diverse ways by Christians and Muslims. Comparative Theology is offered to manage diversity in order to enrich and transform personal spirituality with communal impact. Jesus in Ihya' Ulum ad-Din according to the perspective of Comparative Theology is explore through a qualitative approach with descriptive analysis method. Enrichment and transformation of spirituality through not giving wisdom to those who do not deserve it, not withholding virtue to those who deserve it, loving God by not liking the character of sinners, drawing closer to God by distancing yourself from the character of sinners, seeking God's favor by hating the character sinners, do not lie, do not dispute, do not worry much, do not have bad manners, and remain happy even though sickness befell the body and misfortune befell wealth. I love Jesus more and more through Al-Ghazali. Abstrak: Yesus dipahami secara beragam oleh umat Kristen dan Muslim. Teologi Komparatif ditawarkan untuk mengelola keragaman supaya mengayakan dan mentransformasi spiritualitas personal yang berdampak komunal. Yesus dalam Ihya' Ulum ad-Din menurut perspektif Teologi Komparatif ditelusuri melalui pendekatan kualitatif dengan metode deskriptif analisis. Pengayaan dan transformasi spiritualitas melalui tidak memberikan kebijaksanaan kepada orang yang tidak layak menerimanya, tidak menahan kebajikan kepada orang yang layak menerimanya, mencintai Allah dengan tidak menyukai karakter orang berdosa, mendekat kepada Allah dengan menjauhkan diri dari karakter orang berdosa, mencari perkenanan Allah dengan membenci karakter orang berdosa, tidak berbohong, tidak bertengkar, tidak banyak khawatir, tidak berakhlak buruk, dan tetap berbahagia meskipun sakit mendera tubuh dan musibah menimpa kekayaan. Saya semakin mencintai Yesus melalui Al-Ghazali.